A secure near field communication (NFC)-enabled attendance on android mobile for higher education - Ong, David Da Wei; Singh, Manmeet Mahinderjit (2016)
Today, many universities evaluate the performance of students in a semester based on the student’s attendance to class to make sure that they do not miss out any important class.This lead to taking attendance system is an important issue in universities.In this work, a sensor based attendance system is proposed. This approach adopts sensing technology, which is Near Field Communication (NFC).Besides that, this system also includes face detection and recognition function to identify the person that taking attendance is currently being the owner of the NFC tag.This multi-factor identification system will be designed to cater the limitation of the conventional attendance system.The final results demonstrate that the proposed system thwart against replaying events leading to duplication s recording and cheating by legitimate and illegitimate users have due to the added randomization effect in generating sessions for each event recorded within the web-service database.The overall system provides an efficient, accurate and portability solution and work well for the real-life attendance environment within the university.